Potensi Ekstrak Kapang Endofit Asal Rimpang Kunyit sebagai Antimalaria dan Antioksidan - Septiana, Eris; bustanussalam, Bustanussalam; Rachman, Fauzy; Simanjuntak, Partomuan (Jurnal Kefarmasian Indonesia, 2017)
Malaria infection is still a public health problem, especially in developing countries, including Indonesia. Malaria infection is usually accompanied by increased free radicals in the body of the patient. This situation will cause decreasing the immune system of the patient. Explorating of new drugs that have antimalarial and also antioxidant activity is very important. Therefore, this study aims to determine in vitro antimalarial and antioxidant activity of endophytic fungi extract origin turmeric from Sukabumi. This study begins with fermentation process of endophytic fungi on the broth medium and ethyl acetate was used to extract the filtrat to gain the test extracts. Heme polymerization inhibition and free radical DPPH scavenging method were used to antimalarial and antioxidant in vitro assay respectively. The results showed that 18 isolates of endophytic fungi have antimalarial activity and one isolate inactive and also all isolates have antioxidant activity. Smi.Cl.6F isolate was the most active isolate on the antimalarial and antioxidant assay with IC50 value of each assay were 1.93 mg/mL and 32.28 mg/L respectively. Therefore, Smi.Cl.6F isolates potentially be used as new antimalarial drugs